Direct methanol fuel cell systems with tri-stage energy management and maximum power point tracking - Yu-Hsiang Huang; Shih-Jen Cheng; Yu-Kang Lo; Huang-Jen Chiu; Shu-Wei Kuo; Tai-Hung Wang (2013 1st International Future Energy Electronics Conference (IFEEC), 2013)
Nowadays, most of portable electronic products are widely equipped with Li-ion battery to provide the sustained energy. Besides, direct methanol fuel cells (DMFCs) are widely researched for portable applications. Above all, it is easily taken as an alternative for charging batteries. However, DMFC is highly affected by methanol crossover rate. Its efficiency is low at low power and higher as the output power increases. Combined with this characteristic and unknown crossover rate makes the tracking of the maximum efficiency point (MEP) difficult. Fortunately, the maximum power point (MPP) is close to MEP. This paper utilizes the maximum power point tracking (MPPT) algorithm to approach the MPP and thus approach MEP. Moreover, in attempt to contain the energy supply, the tri-stage energy management's (TEM's) algorithm is implemented based on power deficit or surplus. The proposed SEPIC converter and the system algorithms will be discussed, and the experiments results are given.